Pengembangan LKPD dengan Pendekatan Saintifik dalam Melatih Keterampilan 4C di Kelas V SD - Mega Mulia; A. Syachruroji; Nana Hendracipta (Jurnal Lensa Pendas, 2024)
This research and development aims to find out how to develop, suitability and response of students to LKPD with a scientific approach in training 4C skills in class V elementary school in theme 2 subtheme 1 of the 2nd learning. This research uses research and development (R&D) methods with a research and development research design by Borg & Gall. The subjects in this research were 28 class V students at Sukabela State Elementary School, Serang City, 2023/2024 academic year using purposive sampling technique. Based on the product validation results, material experts obtained an overall average percentage score of 92% with very appropriate criteria, media expert validation was 89.5% with very appropriate criteria, and language expert validation was 83% with appropriate criteria. So the overall product feasibility percentage reached 88.16% with very feasible criteria, and student responses obtained an average percentage score of 98.1% with very good criteria. Thus, LKPD with a scientific approach in training 4C skills in class V elementary school is very feasible and very good for use in the learning process of students in class V elementary school.